Direct amidation of metallaaromatics: access to N-functionalized osmapentalynes via a 1, 5-bromoamidated intermediate. Issue 18 (7th April 2021) - Wang, Hongjian; Ruan, Yonghong; Lin, Yu-Mei; Xia, Haiping
Abstract : The direct C–H amidation of metallapentalyne has been achieved under mild conditions in which key 1, 5-bromoamidated intermediates was determined. Abstract : The direct C–H amidation or imidation of metallaaromatics with N -bromoamides or imides has been achieved under mild conditions and leads to the formation of a family of N -functionalized metallapentalyne derivatives. A unique 1, 5-bromoamidated species has been identified, and can be viewed as a σ H -adduct intermediate in a nucleophilic aromatic substitution. The 1, 5-addition of both electrophilic and nucleophilic moieties into the metallaaromatic framework demonstrates a novel pathway in contrast to the typical radical process of arene C–H amidation involving N -haloamide reagents.